Comparative Study of Legal Regulations on Cannabis in the Netherlands with Indonesia - Rais, Muh Irham; Sulistyo, Faizin; Ruslijanto, Patricia Audrey (IJBLE Scientific Publications Community Inc., 2024)
Cannabis as a plant that has the potential for medical use, has attracted the attention of various countries in regulating its laws. This study aims to conduct a comparison between the legal regulation of cannabis in the Netherlands and Indonesia, especially in the context of medical utilization. The global paradigm shift towards the use of cannabis for medical purposes is one of the driving factors to understand the differences and similarities in legal approaches between the two countries. Using a comparative analysis method, this study identifies significant differences in the approach to cannabis regulation between the two countries and analyzes the urgency of legal reform in Indonesia. Factors such as patient safety, the development of medical research, and the Netherlands' experience in implementing medical cannabis regulation are important points for consideration of legal reform in Indonesia. The results of this study are expected to contribute to the discussion of legal reform in Indonesia regarding the medical use of marijuana. The conclusions and recommendations generated from this study are expected to be a foothold for wise decision-making in formulating legal policies related to cannabis in order to increase its utilization in the medical field in Indonesia.